Edible Insects from the Perspective of Sustainability—A Review of the Hazards and Benefits - Filip Kłobukowski; Maria Śmiechowska; Magdalena Skotnicka (Foods)
The increasing global population, projected to exceed 9.1 billion by 2050, presents a critical challenge for sustainable food production. Edible insects have emerged as a promising alternative protein source due to their high nutritional value, low environmental footprint, and efficient resource utilization. This review explores the opportunities and challenges of integrating edible insects into food systems. Benefits include their high protein content and quality, low greenhouse gas emissions, low-cost production, and ability to thrive on organic waste. Furthermore, edible insect cultivation requires significantly less land and water compared to traditional livestock. Edible insects are nutritionally rich, containing substantial amounts of essential amino acids, unsaturated fatty acids, and minerals. However, barriers to widespread adoption persist, such as cultural perceptions, regulatory hurdles, potential allergenicity, and biological and chemical contamination. Furthermore, standardizing rearing practices and ensuring food safety are critical for broader adoption. While edible insects represent a nutritious, low-cost food and feed, there are a lot of variables that have not been fully investigated. Only after further research, promising results, and solutions that are relatively easy to apply might edible insects be considered a sustainable food source. Considering the challenges that may arise by 2050, more intensive research is highly advised.